Exploring role of Eco-friendly elevators in literature: Istraživanje uloge ekološki prihvatljivih liftova u literaturi - Zrnić, Nenad; Dragović, Andro; Kosanić, Nenad (Industrija, 2023)
This study is exploring the role of Eco-friendly elevators in literature based on an analysis of 113 papers published in scholarly journals drawn from the Scopus database. This is the first study which used a bibliometric analysis to review the academic literature in the elevator system research field. The analysis started with the gradual classification of collected papers according to the multi-objective problem of vertical transportation and a citation analysis. Determining predominant themes and sub-themes was conducted by bibliometric analysis based on the co-occurrence of title words inside bi-dimensional matrix. The obtained results highlighted an emerging research cluster (energy utilization) one of the most important for future elevator system development. This cluster addresses technological advances of elevators and predicts Eco- elevator technologies to be widely used in near future. This research could be very useful to foster in-depth knowledge of Eco-friendly elevators.